1990
DOI: 10.1577/1548-8675(1990)010<0442:ciwslm>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Wisconsin's Lake Michigan Salmonid Sport Fishery, 1969-1985

Abstract: The modern sport fishery for salmonids in Wisconsin waters of Lake Michigan was begun during 1963-1969 with the stocking of rainbow trout Oncorhynchus mykiss, lake trout Salve/inns namaycush, brook trout 5". fontinalis, brown trout Salmo trulta, coho salmon O. kisutch, and Chinook salmon O. tshawytscha. The fishery grew rapidly during 1969-1985 as angler effort increased 10-fold, catch rate doubled, and catch increased 20-fold. The stocking and catch became increasingly dominated by Chinook salmon, with coho s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Fishing effort and CPE.-In U.S. waters, we used estimates of targeted fishing effort for the boat mode of angling to track changes in fishing effort. Troll fishing from boats is the most effective mode of capturing Chinook Salmon and regularly accounts for about 85% of the within-lake harvest (e.g., Hansen et al 1990;Rakoczy and Svoboda 1997;Benjamin and Bence 2003a). We assumed that boat-mode effort would be the best type of effort to characterize the spatial and temporal changes in the fishery.…”
Section: Methodsmentioning
confidence: 99%
“…Fishing effort and CPE.-In U.S. waters, we used estimates of targeted fishing effort for the boat mode of angling to track changes in fishing effort. Troll fishing from boats is the most effective mode of capturing Chinook Salmon and regularly accounts for about 85% of the within-lake harvest (e.g., Hansen et al 1990;Rakoczy and Svoboda 1997;Benjamin and Bence 2003a). We assumed that boat-mode effort would be the best type of effort to characterize the spatial and temporal changes in the fishery.…”
Section: Methodsmentioning
confidence: 99%
“…Bioenergetics model application to Lake Mich-igan began because of management concern about the predator-prey balance in this highly valuable system, and it showed that bioenergetics models are important and effective tools for investigating otherwise difficult questions. The application of bioenergetics models to Lake Michigan spurred management agencies into reviewing and modifying their management and stocking policies (Hansen 1986;Hansen et al 1990;Keller et al 1990) and to enhancing their monitoring and research programs (Brandt et al 1991). Few would argue, however, that bioenergetics model estimates were precise within ±10% of true values; rather, estimates were reasonable enough to show trends in predator consumption and directions and time scales of expected changes such that a management response was warranted.…”
Section: Management Applicationsmentioning
confidence: 99%
“…Wisconsin's Lake Michigan creel survey, an annual survey since 1969 (Hansen et al 1990), was used to compare the return rate of each stocking strategy in the sport fishery. Most coho salmon observed by creel clerks were weighed to the nearest 0.1 lb (0.45 kg), measured (total length) to the nearest 0.1 in (2.54 mm), and examined for fin clips.…”
Section: Sport Fishery Returnsmentioning
confidence: 99%
“…Before 1984, Wisconsin's Lake Michigan coho salmon stocking program used only yearling coho salmon stocked in the spring at 14-16 months of age and averaging 152 mm in total length (TL) and 22.7 g in weight. This stocking program produced returns to anglers of 5.9% from 1968 to 1984 (Hansen et al 1990and during 1986-1992, Wisconsin stocked accelerated-growth fingerling coho salmon in the fall (Figure 1). These fish were stocked in October or November at 9 months of age and at an average size of 127 mm and 18.2 g. The switch to accelerated-growth fall fingerlings was made to save hatchery space and reduce rearing costs.…”
mentioning
confidence: 99%